A web-based screening tool for near-port air quality assessments. (December 2017) - Isakov, Vlad; Barzyk, Timothy M.; Smith, Elizabeth R.; Arunachalam, Saravanan; Naess, Brian; Venkatram, Akula
Abstract: The Community model for near-PORT applications (C-PORT) is a screening tool with an intended purpose of calculating differences in annual averaged concentration patterns and relative contributions of various source categories over the spatial domain within about 10 km of the port. C-PORT can inform decision-makers and concerned citizens about local air quality due to mobile source emissions related to commercial port activities. It allows users to visualize and evaluate different planning scenarios, helping them identify the best alternatives for making long-term decisions that protect community health and sustainability. The web-based, easy-to-use interface currently includes data from 21 seaports primarily in the Southeastern U.S., and has a map-based interface based on Google Maps. The tool was developed to visualize and assess changes in air quality due to changes in emissions and/or meteorology in order to analyze development scenarios, and is not intended to support or replace any regulatory models or programs. Highlights: C-PORT is a screening air-quality modeling tool that can inform users about potential local air quality impacts in the vicinity of ports. It allows users to visualize, estimate, and compare potential changes in air quality concentrations from different planning scenarios. The web-based, easy-to-use interface currently includes pre-loaded data and options to upload custom inputs for multiple source types. C-PORT has a map-based interface similar to the widely used Google Earth.